Strategi Komunikasi Pemasaran CV. Rintis Usaha Bersama Melalui Media E-Commerce dalam Meningkatkan Penjualan Produk - Rifaldy Rios Wanadri; Iin Soraya; Cindya Yunita Pratiwi (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
The development of e-commerce has transformed companies’ marketing communication strategies, including CV. Rintis Usaha Bersama, which operates in the sales of medical and industrial gas cylinders. Increasing competition has driven the company to optimize its digital communication strategies to enhance sales and maintain its market competitiveness. An effective marketing communication strategy is essential in attracting customers and fostering their loyalty. Therefore, this study aims to analyze the marketing communication strategies of CV. Rintis Usaha Bersama through e-commerce and evaluate their effectiveness in boosting product sales. This research employs a qualitative method with an in-depth interview approach involving the company’s management. The analysis is conducted using the SOSTAC model, which includes situation, objectives, strategy, tactics, action, and control in digital marketing strategies. The findings indicate that CV. Rintis Usaha Bersama implements the 4P marketing communication mix (product, price, place, promotion) through e-commerce platforms such as Shopee and Tokopedia. The strategies adopted include clear product information dissemination, transparent pricing, promotional discounts, paid advertising, and flash sale campaigns. However, the main challenges faced by the company include intense price competition and an increasing number of competitors in the e-commerce sector. To improve the effectiveness of marketing communication strategies, the company is advised to develop educational content about its products, enhance customer engagement through responsive services, and collaborate with influencers or affiliate marketers to expand its audience reach. Regular evaluations are also necessary to ensure the strategies remain relevant to the dynamic market trends.